The Implementation of Conservation Policy and the Application of Solar Energy Technology in Small House Areas: Stockholm, Sweden. (3rd April 2022) - Legnér, Mattias; Femenías, Paula
ABSTRACT: This paper investigates the dynamic between protection of the historic environment and the application of solar energy technology on 1- or 2-family houses in Sweden. More specifically, the building code relating to the installation of photovoltaic (PV) panels on house roofs and how existing policies are implemented in Stockholm City is investigated in order to better understand the challenges in reconciling renewables and the conservation of built heritage. Especially when applied in urban areas PV panels may have a large impact on socio-cultural values, making them difficult to insta where the historic environment is to be protected from large changes. By using a mix of methods (policy analysis, case studies, and interviews) we come to the conclusion that municipalities should develop routines and guidelines that offer homeowners precise information on the potential of solar energy and requirements motivated by concern for the historic environment. Guidelines that are well-known, clear and also require homeowners to dismount exhausted panels could work both to protect built heritage and to promote more use of solar energy in some small house areas.